Dual activity inhibition of threonine aspartase 1 by a single bisphosphate ligand. Issue 53 (30th November 2022) - Höing, Alexander; Struth, Robin; Beuck, Christine; Rafieiolhosseini, Neda; Hoffmann, Daniel; Stauber, Roland H.; Bayer, Peter; Niemeyer, Jochen; Knauer, Shirley K.
Abstract : "Targeting two for the price of one" – a selective bisphosphate ligand allows dual inhibition of threonine aspartase 1 by simultaneously addressing independent key functions – its protein–protein interaction-based activation and enzymatic function. Abstract : Therapy resistance remains a challenge for the clinics. Here, dual-active chemicals that simultaneously inhibit independent functions in disease-relevant proteins are desired though highly challenging. As a model, we here addressed the unique protease threonine aspartase 1, involved in various cancers. We hypothesized that targeting basic residues in its bipartite nuclear localization signal (NLS) by precise bisphosphate ligands inhibits additional steps required for protease activity. We report the bisphosphate anionic bivalent inhibitor 11d, selectively binding to the basic NLS cluster ( 220 KKRR 223 ) with high affinity ( K D = 300 nM), thereby disrupting its interaction and function with Importin α (IC50 = 6 μM). Cell-free assays revealed that 11d additionally affected the protease's catalytic substrate trans -cleavage activity. Importantly, functional assays comprehensively demonstrated that 11d inhibited threonine aspartase 1 also in living tumor cells. We demonstrate for the first time that intracellular interference with independent key functions in a disease-relevant protein by an inhibitor binding to a single site is possible.